PERFORMANCE ANALYSIS OF VILLAGE CONSULTANCY BOARDS (BPD) IN PREPARATION OF VILLAGE REGULATIONS IN BAMBANGIN VILLAGE, BALAWANG DISTRICT, BARITO KUALA (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2023)
The Village Publications Body is a legislative body and a container that serves to accommodate and channel the aspirations of the community. BPD is a working partner of the Government of the Village which has an equal position in organizing the affairs of government, development, and empowerment of the community. Bambangin Village is one of the villages located in Belawang Prefecture, Barito Kuala District, Southern Kalimantan Province. This article is compiled to dig into how the Performance of the Village Public Service in carrying out its functions establishes the village rules, oversees the implementation of the village regulations and the heads of villages regulations. This type of research uses Qualitative with a descriptive approach that describes phenomena occurring in society concerning social problems and performance of BPD in the drafting of the Village Regulations. The results found that the role of Bambangin Village BPD is still weak and not optimal in drawing up the Village Rules, BPD has always been present but tends to agree that just never make a record and initiate other innovative perdes based on the needs of the community, this weakness is due to the capacity of resources I have never received special training about BPD.